White matter signal abnormalities in former National Football League players. Issue 1 (6th November 2017) - Alosco, Michael L.; Koerte, Inga K.; Tripodis, Yorghos; Mariani, Megan; Chua, Alicia S.; Jarnagin, Johnny; Rahimpour, Yashar; Puzo, Christian; Healy, Rose C.; Martin, Brett; Chaisson, Christine E.; Cantu, Robert C.; et al.
Abstract: Introduction: Later‐life brain alterations in former tackle football players are poorly understood, particularly regarding their relationship with repetitive head impacts (RHIs) and clinical function. We examined white matter signal abnormalities (WMSAs) and their association with RHIs and clinical function in former National Football League (NFL) players. Methods: Eighty‐six clinically symptomatic former NFL players and 23 same‐age reportedly asymptomatic controls without head trauma exposure underwent magnetic resonance imaging and neuropsychological testing. FreeSurfer calculated WMSAs. A cumulative head impact index quantified RHIs. Results: In former NFL players, increased volume of WMSAs was associated with higher cumulative head impact index scores ( P  = .043) and worse psychomotor speed and executive function ( P  = .015). Although former NFL players had greater WMSA volume than controls ( P  = .046), these findings are inconclusive due to recruitment of controls based on lack of clinical symptoms and head trauma exposure. Discussion: In former NFL players, WMSAs may reflect long‐term microvascular and nonmicrovascular pathologies from RHIs that negatively impact cognition. Highlights: Repetitive head impact exposure was positively associated with WMSAs in former NFL players. In former NFL players, greater WMSAs was associated with worse psychomotor speed and executive function. The pathologies of WMSAs may contribute to the clinical presentation of chronic traumatic encephalopathy.